Prospects of Indian traditional fermented food as functional foods - CHAUDHARY, ANITA; SHARMA, D K; ARORA, ANJU (The Indian Journal of Agricultural Sciences, 2018)
The burgeoning population of the developing countries, climate change and shrinking resources are putting pressure on the food security. Thus it implies that in future we not only have to produce more but also do smart agriculture for sustaining on this planet. Moreover, in the era of globalization, people are looking more towards the healthy food, which can provide the nutrients, vitamins and minerals to the body. Hence, in future, the consumption of fermented food is going to increase not only across the world, but also in the developing countries. Traditionally people of India are trying to preserve the food with the fermentation and unknowingly, they are able to produce more nutritious and healthy food, which is able to alleviate many health problems. Scientific evidence has now started emerging in support of the traditional practices being practiced in the ancient times. However, the traditional practice of producing fermented food need to be done scientifically, as sometimes uncontrolled fermentation have led to the spoiled food, due to production of some toxic substances such as bacterial and mold toxins, which instead of providing benefits to the human beings may harm them.